The Portuguese policy for building acoustics assessement - Patrício, J. (2012)
This paper presents the Portuguese policy to assess the overall acoustic quality of residential buildings, in order to issue the corresponding permission for use and trade them within the urban market. The Portuguese policy rely on the legal frame set forth by the national Building Acoustics code, which imposes the existence of an acoustic project for each new building, covering the sound insulation in terms of airborne and impact noise, and requirements for service equipment noise and reverberation times. The assessment is done by testing after the construction has been completed and when all the service equipment is installed and operating accordingly. The tests have to be done by accredited laboratories. In order to avoid testing all possibilities in terms of partitions, service equipment, volumes and surfaces, a simplified sampling is adopted.